Pengembangan Game Edukasi Berhitung (Counting Object) untuk Meningkatkan Kemampuan Numerasi Anak Usia Dini - Nani Mazjiatul Adni; Ika Rachmayani; Gunawan Gunawan; Baik Nilawati Astini (Indonesian Publication Center, 2024)
This research aims to develop an effective, feasible, and practical educational counting game (counting object) media to enhance the numeracy skills of 5-6-year-old children at TK Jannatul Adni Aikmel Timur. The research employed a Research and Development (R&D) methodology with the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. The research subjects were 10 children aged 5- 6 years at TK Jannatul Adni. Data collection techniques included observation, interviews, questionnaires, and documentation. The results showed that the educational counting game (counting object) media was effective in improving the numeracy skills of 5-6-year-old children at TK Jannatul Adni Aikmel Timur. This was evident in the results of the media trials with children, where the first development stage achieved a percentage of 76.25%, and the second development stage achieved a percentage of 92%. Therefore, the educational counting game (counting object) media is effective in enhancing early childhood numeracy skills. The media was also declared feasible by media and material experts and deemed practical for use by teachers and children.